Produksi dan Kandungan Mineral Pueraria phaseoloides dengan Tingkat Naungan dan Inokulasi Mikoriza Berbeda - A.I.M Ali; Yakup Yakup; Sabaruddin Sabarudin (Faculty of Animal Science, Bogor Agricultural University, 2010)
Problems of forage management in the integration of livestock into oil palm and rubber plantations in Indonesia are declining of light as the canopy of the plant increases and acid soils containing low available P, Cu, and Zn. The objective of experiment was to study the effect of shading and arbuscular mycorrhizal fungi (AMF) inoculations on the production and content of P, Cu, and Zn of Pueraria phaseoloides (Roxb.) Benth (puero). The experiment was arranged according to the split plot design with three replicates in a green house. Treatments tested were shading as the main plot (0%, 25%, 50%, and 75%) and AMF inoculations as sub plots (indigenous AMF, Glomus manihotis, indigenous AMF + G. manihotis and no inoculation). Root biomass was affected by shading level while leaf stem ratio was affected by both shading level and AMF inoculations. Inoculations with G. manihotis and indigenous + G. manihotis indicated higher herbage production and P contents than inoculations with indigenous AMF. Effectiveness of AMF inoculation on improvement of production and P uptake varied according to shading conditions. P. phaseoloides was tolerant to shading up to 50% and its production and P content as responses on inoculation of AMF were affected by soil conditions and shading intensity. Inoculation of G. manihotis and its combination with indigenous AMF improved production and P content of Pueraria phaseoloides in shading level upto 50%.